2022
DOI: 10.1098/rsos.202202
|View full text |Cite
|
Sign up to set email alerts
|

Advertising cooperative phenotype through costly signals facilitates collective action

Abstract: Around the world, people engage in practices that involve self-inflicted pain and apparently wasted resources. Researchers theorized that these practices help stabilize within-group cooperation by assorting individuals committed to collective action. While this proposition was previously studied using existing religious practices, we provide a controlled framework for an experimental investigation of various predictions derived from this theory. We recruited 372 university students in the Czech Republic who we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 64 publications
1
14
0
Order By: Relevance
“…For comparison, while the probability of selecting the revealed group in the high cost condition in Lang et al' study (2022) was 57% for cooperators, it was only 38% in the current study. The prospect of multiple PGG rounds likely contributed to increasing the signal's reliability in the eyes of cooperators in the Lang et al (2022) study, while many cooperators in the current study would distrust the one-shot signal. Interestingly, the low cost signal successfully repelled participants with selfish strategies (only 14% chose the revealed group in the low cost condition).…”
Section: Discussion Of Studymentioning
confidence: 85%
See 3 more Smart Citations
“…For comparison, while the probability of selecting the revealed group in the high cost condition in Lang et al' study (2022) was 57% for cooperators, it was only 38% in the current study. The prospect of multiple PGG rounds likely contributed to increasing the signal's reliability in the eyes of cooperators in the Lang et al (2022) study, while many cooperators in the current study would distrust the one-shot signal. Interestingly, the low cost signal successfully repelled participants with selfish strategies (only 14% chose the revealed group in the low cost condition).…”
Section: Discussion Of Studymentioning
confidence: 85%
“…These opportunity costs often serve as costs associated with ultra-cooperative groups (Iannaccone, 1992), yet it is unclear whether they may also reliably assort cooperators during intergroup conflict. From the game-theoretical perspective, including positive rather than negative costs should not affect the between-and within-group dynamics, but we wager that such a change might significantly impact signaler and receiver psychology (Lang et al, 2022;Soler, 2012). If these positive and negative costs would indeed differently motivate participants' gameplay and, especially, the decision to sacrifice and hurt the outgroup, these results could help us better understand how some ultra-cooperative groups may motivate their members to commit self-sacrificial violent acts (Iannaccone & Berman, 2006).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The reviewed evidence suggests that costly religious signals reliably communicate trustworthiness to other co‐religionists, and that people can use this group‐specific form of communication to sustain cooperation and reciprocity with other members of religious communities. Interestingly, despite some supportive evidence from laboratory experiments (Lang et al., 2022), the sparse research conducted outside religious traditions suggests that costly commitment signalling may not be effective in real‐world secular contexts. First, using archival data on the survival of US 19th‐century utopian communes, Sosis and Bressler (2003) showed that while the frequency of costly group practices (taboos, collective rituals) was associated with commune longevity (presumably due to increased intra‐group trust and cooperation), this effect was higher in religious communes compared to secular communes.…”
Section: Introductionmentioning
confidence: 99%